the Effect of Treatment on Serum C3, C4, IL-10, IL1-β, IL-6, TNF-α in Patients with Systemic Lupus Erythematosus : Serum C3 and C4, IL-10, IL1-β, IL-6, TNF-α in SLE - Reyimu, Nadira; Jing, Yueyue (Journal of Medical Biochemistry, 2025)
-
Keywords: Serum Complement C3, Complement C4, IL-10, IL1-β, IL-6, TNF-α, systemic lupus erythematosus, Libman-Sacks endocarditis